CCOG: A web‐based cognitive test tool for detecting neurodegenerative disorders. Issue 1 (25th August 2020) - Rhodius‐Meester, Hanneke F.M.; Paajanen, Teemu; Koikkalainen, Juha; Mahdiani, Shadi; Bruun, Marie; Baroni, Marta; Lemstra, Afina W.; Scheltens, Philip; Herukka, Sanna‐Kaisa; Pikkarainen, Maria; Hall, Anette; Hänninen, Tuomo; et al.
Abstract: Introduction: Web‐based cognitive tests have potential for standardized screening in neurodegenerative disorders. We examined accuracy and consistency of cCOG, a computerized cognitive tool, in detecting mild cognitive impairment (MCI) and dementia. Methods: Clinical data of 306 cognitively normal, 120 mild cognitive impairment (MCI), and 69 dementia subjects from three European cohorts were analyzed. Global cognitive score was defined from standard neuropsychological tests and compared to the corresponding estimated score from the cCOG tool containing seven subtasks. The consistency of cCOG was assessed comparing measurements administered in clinical settings and in the home environment. Results: cCOG produced accuracies (receiver operating characteristic‐area under the curve [ROC‐AUC]) between 0.71 and 0.84 in detecting MCI and 0.86 and 0.94 in detecting dementia when administered at the clinic and at home. The accuracy was comparable to the results of standard neuropsychological tests (AUC 0.69–0.77 MCI/0.91–0.92 dementia). Discussion: cCOG provides a promising tool for detecting MCI and dementia with potential for a cost‐effective approach including home‐based cognitive assessments.